Pengaruh Kualitas Pelayanan Terhadap Keputusan Berkunjung Kembali di Restoran Mega Wisata Bonjol - Yudha Fatmiruftian Syahril; Feri Ferdian (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
This research was motivated by the discovery of problems related to service quality and the decision to revisit the Mega Wisata Bonjol Restaurant. The aim of this research is to analyze how much influence service quality has on the decision to revisit Mega Wisata Bonjol. This research includes quantitative descriptive research with causal associative methods used. This research variable includes indicators of service quality as independent variables which include reliability, responsiveness, assurance, empathy, and tangibles. Meanwhile, the dependent variable is the decision to visit again which includes interest in visiting again, reference for visiting and preference for visiting. Obtaining primary and secondary data using data collection techniques through field observations, questionnaires and literature studies. The population in this study were customers of Mega Wisata Bonjol Restaurant with a sample of 228 people. The data collection technique in this research uses a purposive sampling technique, namely data collection is carried out by distributing questionnaires to customers and then processed using SPSS version 20.00. The results are stated that the overall service quality is included in the good category on a scale of 5 with an average value of 3. 8. The overall decision to revisit is included in the very good category on a scale of 5 with an average value of 4.7. With a regression coefficient of 0.157 with a sig value. 0.02 < 0.05. This means that for every 1 unit increase in service quality, the decision to return to visit will increase by 0.157 units. Furthermore, an R square value of 0.336 was obtained, meaning that the influence of variable (X) on variable (Y) was 33.6%. Meanwhile, 66.4% was influenced by other factors.